Islamic Banking Practices - Razli Ramli, Mohammad Khairi Saat (Ibfim, 2014)
This book is a special gift from IBFIM to those who are serious to learn the practical aspect of islamic banking. Many of the materials inside are actually from the experiences of the writers. It is hoped that this book can continue to assist many students and practitioners in understanding mechanisms embedded in the operations of Islamic banking.